COVID-19, Alcohol Consumption and Stockpiling Practises in Midlife Women: Repeat Surveys During Lockdown in Australia and the United Kingdom - Miller, Emma R.; Olver, Ian N.; Wilson, Carlene J.; Lunnay, Belinda; Meyer, Samantha B.; Foley, Kristen; Thomas, Jessica A.; Toson, Barbara; Ward, Paul R. (Frontiers in Public Health, 2021)
Introduction: This project examined the impact of COVID-19 and associated restrictions on alcohol practices (consumption and stockpiling) and perceptions of health risk among women in midlife (those aged 45 to 64 years). Methods: We collected online survey data from 2437 midlife women in the United Kingdom (UK) and Australia in May 2020, recruited using a commercial panel, in the early days of mandated COVID-19 related restrictions in both countries. Participants were surveyed again (N=1377) in July 2020, at a time when COVID-19 restrictions were beginning to ease. The surveys included the Alcohol Use Disorder Identification Test – Consumption (AUDIT-C) and questions alcohol stockpiling. Analysis involved a range of univariate and multivariate techniques examining the impact of demographic variables and negative affect on consumption and acquisition outcomes. Results: In both surveys (May and July), UK women scored higher than Australian women on the AUDIT-C, and residence in the UK was found to independently predict stockpiling of alcohol (RR:1.51; 95% CI: 1.20, 1.91). Developing depression between surveys (RR:1.53; 95% CI: 1.14, 2.04) and reporting pessimism (RR:1.42; 95% CI: 1.11, 1.81) and fear/anxiety (RR: 1.33; 95% CI: 1.05, 1.70) at the beginning of the study period also predicted stockpiling by the end of the lockdown. Having a tertiary education was protective for alcohol stockpiling at each timepoint (RR: 0.69; 95% CI: 0.54, 0.87). Conclusions: COVID-19 was associated with increases in risky alcohol practices that were predicted by negative emotional responses to the pandemic. Anxiety, pessimism and depression predicted stockpiling behaviour in UK and Australian women despite the many demographic and contextual differences between the two cohorts. Given our findings and the findings of others that mental health issues developed or were exacerbated during lockdown and may continue long after that time, urgent action is required to address a potential future pandemic of alcohol-related harms.